Benefit of Protected Fat for Improving Production and Reproduction of Ruminant - Wina, Elizabeth; R, Susana I W (Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Fat or free fatty acid is one of the energy sources which is high density and gives higher energy than any other nutrients. Indonesia has a huge potency for free fatty acid as alternative energy source for ruminant. However, in a certain amount, fat or fatty acid will cause negative effect on the rumen function. Therefore, several technologies to protect fat or fatty acid were developed. In early lactation, dairy cow requires additional energy from high density ingredient without causing any negative effect on rumen function. This paper describes fat metabolism in the rumen and post rumen, technology to protect fat or free fatty acid and the effect of protected fat or fatty acid on nutritional value, production and reproductive performances, carcass quality and milk quality. In conclusion, the utilization of protected fat or fatty acid gives positive effects on productive and reproductive performances. Â  Key words: Fat, fatty acid, protection, metabolism, ruminant